Single‐Atomic Iron Doped Carbon Dots with Both Photoluminescence and Oxidase‐Like Activity. Issue 37 (19th August 2022) - Li, Xin; Ding, Shichao; Lyu, Zhaoyuan; Tieu, Peter; Wang, Maoyu; Feng, Zhenxing; Pan, Xiaoqing; Zhou, Yang; Niu, Xiangheng; Du, Dan; Zhu, Wenlei; Lin, Yuehe
Abstract: Multifunctional nanozymes can benefit biochemical analysis via expanding sensing modes and enhancing analytical performance, but designing multifunctional nanozymes to realize the desired sensing of targets is challenging. In this work, single‐atomic iron doped carbon dots (SA Fe‐CDs) are designed and synthesized via a facile in situ pyrolysis process. The small‐sized CDs not only maintain their tunable fluorescence, but also serve as a support for loading dispersed active sites. Monoatomic Fe offers SA Fe‐CDs exceptional oxidase‐mimetic activity to catalyze 3, 3′, 5, 5′‐tetramethylbenzidine (TMB) oxidation with fast response ( V max = 10.4 nM s ‐1 ) and strong affinity ( K m = 168 µM). Meanwhile, their photoluminescence is quenched by the oxidation product of TMB due to inner filter effect. Phosphate ions (Pi) can suppress the oxidase‐mimicking activity and restore the photoluminescence of SA Fe‐CDs by interacting with Fe active sites. Based on this principle, a dual‐mode colorimetric and fluorescence assay of Pi with high sensitivity, selectivity, and rapid response is established. This work paves a path to develop multifunctional enzyme‐like catalysts, and offers a simple but efficient dual‐mode method for phosphate monitoring, which will inspire the exploration of multi‐mode sensing strategies based on nanozyme catalysis. Abstract : Single‐atomic Fe doped carbon dots (SA Fe‐CDs) with both oxidase‐like activity and luminescence are synthesized using a simple pyrolysis protocol with NaFeEDTA as a precursor. Dual‐mode colorimetric and fluorometric quantification of phosphates with good performance is achieved by utilizing the specific inhibition impact of phosphates on SA Fe‐CDs.